PROFITABILITAS DAN RETURN SAHAM: PERAN MODERASI ARUS KAS OPERASI DAN UKURAN PERUSAHAAN - Murni Prasetyaningrum (Fakultas Bisnis UKDW, 2013)
This study aims to determine the effect of profitability on stock returns with operating cash flow and firm size as a moderating variable of companies listed on the Indonesia Stock Exchange in 2006-2008. The population in this study is all companies listed on the Indonesia Stock Exchange. Sample is taken by using purposive sampling method. The hypothesis is tested using regression with variable moderation. Results of this study show that profitability has a positive effect on stock returns, operating cash flow does not significantly moderate the relationship between profitability and stock returns, firm size does not moderate the relationship between profitability and stock returns. Keywords: profitability, stock returns, operating cash flow, size